Menabung Dengan Cerdas: Tabungan Edukasi Untuk Siswa Sekolah Dasar - Arian Yusuf Wicaksono; Farid Dediansyah; Didik Puji Wahyono; Yushinta Alya Purti; Eli Indria (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
This article discusses the importance of saving for basic students in Sawu Hamlet, Sumberjo, Lamongan, as a proactive step in building financial literacy from an early age. The main focus is to provide an in-depth understanding of the concepts of saving, money management and financial planning through an educational approach that is packaged creatively, interestingly and can be applied in everyday life. The results of this study provide insight into the effectiveness of this program in forming wise saving habits from an early age